Proctoring test: an attempt to improve fairness during online assessment / Nursyuhada Azzman and Mohd Nadzri Mohd Najib - Azzman, Nursyuhada; Mohd Najib, Mohd Nadzri (Universiti Teknologi MARA, Pulau Pinang, 2021)
The recent pandemic has forced an overhaul to the overall approach towards education delivery in Malaysia in general, and UiTM specifically. One of the main aspects which have been modified is the evaluation of the taught materials. The current honour system implemented in UiTM, which requires every student to pledge their honesty during all evaluation processes, covers the legal aspect for the tertiary education provider. However, it does not guarantee that these pledges are upheld. Recent student work suggests that the pressure to provide the best answer during an online exam, tempts the students to violate their respective pledges. Hence, a proctored test is conducted to improve and ensure fairness among students during the online test session. In our recent approach, students were observed using video monitoring. Students were required to switch on the camera of their devices and share the entire screen during the online test. The proctored session was recorded and reviewed at a later time. Many issues and limitations were found in this first attempt, mainly due to internet connectivity issues, technical issues and device issues. Hence, improvement to the current proctoring method is suggested in this study. Improvements to the proctoring session include a two-device approach, live proctoring, using other platforms, and providing detailed guidance to avoid technical issues. While a live proctoring session with a set number of students monitored by an invigilator is best to ensure fairness, this approach is difficult to implement when dealing with a large number of students, and minimal invigilators.